SOATTING OF UREA FERTILIZER AND CONCENTRATION LEVEL OF SEAWEED CARRAGINAN Eucheuma cottonii - Rijoly, Stefano; Killay, Amos; Rupilu, Joseph A (RUMPHIUS, 2020)
Euchema cottonii seaweed as carrageenan-producing, growth and development is in need of the quality of light and nutrients such as nitrogen, such as urea. This study aims to determine the combination of long soaking and urea concentration levels that are effective in improving the content of Euchema carrageenan cottonii. This research method uses long immersion urea treatment 2 hours, 4 hours, 6 hours and without immersion (control) and urea concentration of 1 gram, 1,5 gram, 2 gram and wihout of urea fertilizer (control), repeat 3 times. The content of carrageenan in each treatment will be analyzed using ANOVA, followed by HSD test at 95% significance level. The results showed that the best carrageenan content (66.52%) in the treatment of long soaking 2 hours with 2 grams of urea concentration and carrageenan content of the lowest (51.33%) obtained in the treatment of long immersion 6 hours with 1 gram of urea concentration. Carrageenan seaweed Eucheuma cottonii on research generally meets the standards of quality carrageenan for maximum moisture content 35% (SNI Indonesia), and ash content of 15-40% (FAO, FCC), a maximum of 35% (EEC).